Analisis Rasio Keuangan Untuk Memprediksi Kondisi Financial Distress (Studi Empiris Pada PT Gudang Garam Tbk Periode 2018-2020) - Hasanuddin Hasanuddin; Muhammad Ridwan Basalamah; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract Financial reports can be used as a basis for measuring the financial distress of a company by analyzing existing financial ratios.  The aim of this study is to find out and analyze whether the liquidity ratio (current ratio, quick ratio, cash ratio), leverage ratio (debt ratio, debt to equity ratio), profitability ratio (return on assets, return on equity), and activity ratio (inventory turnover, total asset turnover) can be used to predict financial distress conditions at PT.  Gudang Garam Tbk and whether the company went bankrupt or not.  This research was conducted at PT.  Gudang Garam Tbk for the 2018-2020 period.  This study used a tabulated method using Excel software and a Modified Altman Z-Score Model (Z-Score).  The data analysis technique used in this study is secondary data using industry standards.  The results of this study indicate that liquidity ratios, profitability ratios, and activity ratios can be used to predict financial distress at PT.  Gudang Garam Tbk.  Meanwhile, the leverage ratio cannot be used to predict financial distress at PT.  Gudang Garam Tbk. Keywords: Financial Distress, Liquidity, Leverage, Profitability, Activity